Rapid changes in overnight blood pressure after transitioning to early-morning shiftwork. Issue 3 (9th August 2021) - McHill, Andrew W; Velasco, Josie; Bodner, Todd; Shea, Steven A; Olson, Ryan
Abstract: Risk for adverse cardiovascular events increases when blood pressure does not decrease at night ("non-dipping, " <10% decrease from daytime blood pressure). Shiftwork alters relationships between behaviors and endogenous circadian rhythms (i.e., circadian disruption along with variable sleep timing), and chronic shiftwork increases cardiovascular disease risk. To determine whether transitioning into shiftwork changes the overnight blood pressure dipping pattern, we leveraged a natural experiment that occurs when newly-hired bus operators transition from a daytime training schedule into an early-morning shiftwork or daywork schedule. Twenty participants were studied in a 90-day protocol upon new employment and underwent cardio-metabolic health assessments, including ambulatory blood pressure monitoring, and weekly sleep-wake diaries. Measurements were repeated after ~30 and 90 days after transitioning to a day or an early-morning shiftwork schedule. Newly-hired shiftworkers displayed dramatic changes in overnight blood pressure, with 62% converting from a healthy dipping blood pressure to the nondipping pattern, resulting in 93% of shiftworkers displaying a nondipping phenotype at 90-days. In contrast, 50% of dayworkers had a nondipping profile at baseline and this decreased to 0% at 90-days, a significant difference from shiftworkers ( p = .001). At 90-days, overnight blood pressure dipping was ~7% less in shiftworkers than dayworkers (–6.3% [95%CI –3.7 to –8.8%] vs –13.1% [–10.3 to –15.9%]: p < .01), with changes in dipping associated with changes in sleep timing variability ( r 2 = .28, p = .03). The observed changes in overnight blood pressure dipping in newly-hired early-morning shiftworkers, which were associated with sleep timing variability, may be an early warning sign of increased cardiovascular risk among shiftworkers.